If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(-2x + 1) = 2 Reorder the terms: 5x + -1(1 + -2x) = 2 5x + (1 * -1 + -2x * -1) = 2 5x + (-1 + 2x) = 2 Reorder the terms: -1 + 5x + 2x = 2 Combine like terms: 5x + 2x = 7x -1 + 7x = 2 Solving -1 + 7x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 7x = 2 + 1 Combine like terms: -1 + 1 = 0 0 + 7x = 2 + 1 7x = 2 + 1 Combine like terms: 2 + 1 = 3 7x = 3 Divide each side by '7'. x = 0.4285714286 Simplifying x = 0.4285714286
| 2x+6+x+1=3(x-1)+6 | | 3x^2-8y^2=-5 | | 2/10➗3/100 | | 0=-18v^2+1476v-26600 | | 3(x-3)+4=2[-(x-5)-4(2x+1)] | | 4a^2+4a=-15 | | 4a^2+4=-15 | | 2x^1-1=0 | | 5x+60=5x | | 449/0.42= | | 16/5-20x=8 | | 2500+100x+x^2= | | log(5x+1)=1.2 | | y8/y3 | | 6+k^7=-2 | | 3x^3-5x-1=0 | | (36x^4+9)=0 | | 0.05(0.3x-0.06)= | | logx^729=3 | | 4n+5=2n+8 | | logx^36=2 | | 4y+49=27y+7 | | 4y+36=27y+7 | | 4.8x-4=4(1.2x-1) | | 4y+1636=27y+7 | | 8x-5x=x+8 | | 4y+25=27y+7 | | 4y+16=27y+7 | | y+2.4=7.33 | | 8+3n-5=9n+9-5 | | 2[2(3x-1)+3]-2(2x+5)=2(3x-3) | | 4+t^3=-3 |